2019
DOI: 10.1007/s11239-019-01816-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of different risk factor profiles in patients with mesenteric venous thrombosis and systemic venous thromboembolism: a population-based study

Abstract: It is unknown whether the risk factor profile for mesenteric venous thrombosis (MVT) is different from systemic venous thromboembolism (VTE). The aim of the present population-based study was to compare acquired and inherited risk factors in MVT versus VTE. Identification of all MVT patients at Skåne University Hospital between 2000 and 2015 was performed in patient records and AuriculA (Swedish anticoagulation registry). VTE patients were retrieved from the Malmö Thrombophilia Study (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, when comparing the contemporary series from high-income versus low- to middle-income countries, there was no difference in bowel resection and 30-day mortality rate. Regarding long-term mortality, there was no difference between patients with MVT and systemic venous thromboembolism in a population-based study from Sweden ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when comparing the contemporary series from high-income versus low- to middle-income countries, there was no difference in bowel resection and 30-day mortality rate. Regarding long-term mortality, there was no difference between patients with MVT and systemic venous thromboembolism in a population-based study from Sweden ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality, with increased risk of intestinal infarction 45 and risk of recurrence 41 of MVT linked to thrombophilia, compared with overall mortality from MVT, makes it advisable to systematically screen these patients for thrombophilia and to consider lifelong anticoagulant therapy, especially in the absence of a reversible risk factor. 10 We consider personal or family history of peripheral venous thrombosis as a risk factor for MVT, especially in the absence of a known underlying disease, as reported in the literature. 37,46 Among the pathogenic mechanisms of MVT categorized by Zarrouk et al 5 as "local venous congestion," we found three patients with liver cirrhosis, a comorbidity with an obvious poor prognosis in our series, where 100% of patients died in the perioperative period.…”
Section: Breast Cancermentioning
confidence: 99%
“…37,46 Among the pathogenic mechanisms of MVT categorized by Zarrouk et al 5 as "local venous congestion," we found three patients with liver cirrhosis, a comorbidity with an obvious poor prognosis in our series, where 100% of patients died in the perioperative period. Patients with MVT have a different risk factor profile than patients with systemic thromboembolism, 10 showing a higher prevalence of cancer. Malignancy has long been Journal of Vascular Surgery: Venous and Lymphatic Disorders recognized as a risk factor for hypercoagulability and has been reported to be present in 4% to 16% of patients with acute MVT.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation